2016
DOI: 10.6018/analesps.32.2.205061
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre estilos parentales, intensidad psicopatológica y tipo de sintomatología en una muestra clínica adolescente.

Abstract: An investigation was conducted to analyze the relationship between perceived parenting styles, presented intensity psychopathology and externalizing-internalizing dimensions in a clinical sample of adolescents aged 13 to 18. The results found indicate that the psychopathological intensity is associated with age, with older age and over intensity; and with female gender. Only two dimensions of perceived parenting style were found related to psychopathological intensity: psychological control negatively and humo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
(31 reference statements)
1
9
0
2
Order By: Relevance
“…After removing duplicates, a first screening based on title and abstracts resulted in 167 articles. Finally, after a full-text read-through, 59 studies [31,36,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98] were selected for inclusion (see Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates, a first screening based on title and abstracts resulted in 167 articles. Finally, after a full-text read-through, 59 studies [31,36,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98] were selected for inclusion (see Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding our main research goal, i.e., establishing the correlation between parental psychological control and mental health (emotional and behavioral problems), the results from the OR test indicate that, as a general rule, parental psychological control is a risk factor for both internalizing and externalizing emotional and behavioral problems. In this regard, our research into the connection between these variables has singled out psychological control as one of the leading factors underlying emotional disorders among minors [15,59]—both internalizing [18,28,29,30] and externalizing [60].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, based on subjects who perceive high psychological control, the likelihood of externalizing problems is notably higher than that of internalizing problems. This overlaps to a large degree with results from a clinical sample—utilizing the same tools to measure psychological control (EES-C)—which concludes that adolescents score higher on externalizing symptoms and a higher risk of externalizing symptoms, associated to psychological control [59]. These similarities may be due to the criteria that were used to identify participants who had emotional and behavioral problems in their teenage years [52], which would confirm the usefulness of the SDQ scale as a tool for the detection of mental health problems [49,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Research about this concept has obtained less consistent results [32], especially in different cultural contexts [14,16]. Some studies have found that greater parental control is related to adolescents’ better psychological adjustment [32,33,34,35], fewer antisocial and criminal activities [34,36], and a later sexual initiation [37], whereas others find a negative effect related to emotional [36,38,39,40] and behavioral problems [41]. Similarly, some studies have found a positive relationship between parental behavioral control and academic performance in European-American teenagers, but not in African-American ones [33], whereas others have found no association [35] or a negative association [25].…”
Section: Introductionmentioning
confidence: 99%